White-to-Beige and Back: Adipocyte Conversion and Transcriptional Reprogramming - Stanislav Boychenko; Vera S. Egorova; Andrew Brovin; Alexander D. Egorov (MDPI AG, 2024)
Obesity has become a pandemic, as currently more than half a billion people worldwide are obese. The etiology of obesity is multifactorial, and combines a contribution of hereditary and behavioral factors, such as nutritional inadequacy, along with the influences of environment and reduced physical activity. Two types of adipose tissue widely known are white and brown. While white adipose tissue functions predominantly as a key energy storage, brown adipose tissue has a greater mass of mitochondria and expresses the uncoupling protein 1 (UCP1) gene, which allows thermogenesis and rapid catabolism. Even though white and brown adipocytes are of different origin, activation of the brown adipocyte differentiation program in white adipose tissue cells forces them to transdifferentiate into "beige" adipocytes, characterized by thermogenesis and intensive lipolysis. Nowadays, researchers in the field of small molecule medicinal chemistry and gene therapy are making efforts to develop new drugs that effectively overcome insulin resistance and counteract obesity. Here, we discuss various aspects of white-to-beige conversion, adipose tissue catabolic re-activation, and non-shivering thermogenesis.